Traditional Chinese Medicine Monomers: Novel Strategy for Endogenous Neural Stem Cells Activation After Stroke - Wang, Ju; Hu, Jun; Chen, Xuezhu; Lei, Xuejiao; Feng, Hua; Wan, Feng; Tan, Liang (Frontiers in Cellular Neuroscience, 2021)
Stem cell therapy has become a potential regenerative medical treatment and a promising approach for treating brain injuries induced by different types of cerebrovascular disease and has a variety of application methods. The activation of endogenous neural stem cells (NSCs) can replace infarcted neurons and promote the regeneration of neural networks without the technical and logistical problems associated with the transplantation of exogenous stem cells and can be a feasible strategy to treat central nervous system (CNS) injury. The potential molecular mechanisms of drug therapy for the activation of endogenous NSCs have gradually been revealed by researchers. Traditional Chinese medicine monomers (TCMs) are active components extracted from Chinese herbs, and some of them have demonstrated the potential to induce the regeneration of NSCs in CNS diseases. Panax notoginseng saponins (PNS), ginsenoside Rg1, astragaloside IV (AST), icariin (ICA), salvianolic acid B (Sal B), resveratrol (RSV), curcumin, artesunate (ART) and ginkgolide B （GB） have different effects on NSCs and induce many signaling pathways and molecules, such as Wingless/integrated/β-catenin (Wnt/β-catenin) signaling, sonic hedgehog (Shh) signaling, nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1) and so on. This paper may provide further motivation for researchers to take advantage of TCMs in the study of CNS injury and stem cells.